A persistent case of tuberculosis of the pubic symphysis and pubic bone. (10th March 2014) - Dapunt, Ulrike; Mischnik, Alexander; Goeppinger, Stephan; Lehner, Burkhard
Abstract : A case of a patient suffering from tuberculosis of the pubic symphysis and pubic bone is presented. There were no symptoms other than pain in the right groin area for 12 months. An X-ray of the pelvis showed an osteodestructive lesion of the pubic bone, and an MRI revealed an abscess formation of the pubic symphysis. Tissue samples were collected via CT-guided needle biopsy. Histological evaluation of tissue and analysis by PCR prompted the diagnosis of musculoskeletal tuberculosis. Despite antituberculous chemotherapy according to the current guidelines, the osteodestructive lesion progressed. This case highlights the difficulty of treating bone infections in general. Moreover, Mycobacterium tuberculosis as a rare causative agent of bone infections is discussed.